2009
DOI: 10.3109/01913120903275626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dobutamine and Hyperoxia on Free Radicals Production in Relation to the Ultrastructural Alterations in the Endothelial of Myocardial Capillary in Rats,Rattus norvigicus

Abstract: Hyperoxia has been widely used as model for oxidative stress. Free radicals (FR), suproxide anion (*O(-)(2)) and nitric oxide anion (*NO(-)), are highly toxic and have detrimental effects on nitroso-redox balance in the myocyte. Myocardium is rich with beta-adrenergic receptors and endothelial is the site of NO production. The authors hypothesized that graded doses of dobutamine result in hyperkinetic state, which shifts the nitroso-redox balance toward the buildup of reactive species in dose-dependent excess.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Using 10 mm as a cutoff line for measuring the capillaries (<10 mm) and small arteries/ veins (>10 mm), we found that the PD cases had fewer capillaries (in the RN) and more small arterioles/veins (in the LC) with a significant reduction in the ratio of small/large vessels throughout all nuclei. The data suggest that vessel degeneration in PD cases was primarily at the level of capillaries, which may themselves be more vulnerable to degeneration than the small arteries/veins, and/or to the enlarged capillaries as a result of vascular remodeling (27). The transformation of the microvasculature from predominantly capillaries to predominantly small arterioles/venules has a profound effect on oxygen diffusion.…”
Section: Discussionmentioning
confidence: 91%
“…Using 10 mm as a cutoff line for measuring the capillaries (<10 mm) and small arteries/ veins (>10 mm), we found that the PD cases had fewer capillaries (in the RN) and more small arterioles/veins (in the LC) with a significant reduction in the ratio of small/large vessels throughout all nuclei. The data suggest that vessel degeneration in PD cases was primarily at the level of capillaries, which may themselves be more vulnerable to degeneration than the small arteries/veins, and/or to the enlarged capillaries as a result of vascular remodeling (27). The transformation of the microvasculature from predominantly capillaries to predominantly small arterioles/venules has a profound effect on oxygen diffusion.…”
Section: Discussionmentioning
confidence: 91%
“…A widely held view is that oxygen toxicity arises from increased oxygen free radical generation in cells (Beckman and Ames 1998; Mattar and Haffor 2009), and it has been observed that exposure to hyperoxia accelerates the accumulation of oxidative by-products such as lipofuscin (von Zglinicki et al 1995), which would seem to support the hypothesis.…”
Section: Introductionmentioning
confidence: 98%
“…Simvastatin reduces mitochondrial stress in myocytes [50], yet effects on neurons is unknown. Statins may contribute to cognitive reserve in PD by reducing ROS in the medial frontal gyrus/cortex, an area found to exhibit increased vascular burden in PD [49].…”
Section: Discussionmentioning
confidence: 99%